Pembuatan Sistem Informasi Monitoring dan Evaluasi Member Klinik Ummat Manang - Harjanto, Sri; Sefriani, Eka Widya; Tri Vulandari, Retno (Redtech Putra Benua, 2025)
Monitoring and evaluation (Monev) activities play a crucial role in overseeing the implementation of a program. However, clinic management has not yet optimized member data management due to limited human resources and the existing system. The problem formulation of this practical work is how to develop a web-based monitoring and evaluation information system for members at Klinik Ummat Manang. The presence of this system aims to facilitate clinic staff in monitoring clinic members. During the analysis phase, data collection methods include interviews with clinic representatives, observations, and literature studies. The data sources consist of primary and secondary data. The system design utilizes Unified Modeling Language (UML), while the construction phase employs PHP as the programming language and MySQL as the database management system (DBMS). The software used includes Sublime Text 3 and Laragon as a virtual server. This system is designed to be accessible on both desktop and mobile devices. The expected outcome is the development of a monitoring and evaluation information system for Klinik Ummat members, which simplifies data management and member monitoring for all relevant parties. Keywords: Monitoring and Evaluation System, Web-Based System, Member Management.